Cutaneous Manifestations of Hypothyroidism amongst Gynecological consultations - Saadia, Zaheera; Alzolibani, Abdullateef A.; Al Robaee, Ahmad; Al Shobaili, Hani A.; Settin, Ahmad A (International Journal of Health Sciences, 2010)
Abstract Objectives: Many of the signs of hypothyroidism, affect the skin as well as the genital system of affected female cases. The aim of this study is to highlight the presenting dermatologic and gynecologic manifestations of firstly-diagnosed hypothyroid females. Patients and Methods: This is a case control study that included 150 patients presenting for gynecological consultation. Out of them, 60 were affected with hypothyroidism and 90 were euthyroid based on clinical and laboratory investigation backgrounds. Their gynecologic and dermatologic findings were analyzed and compared statistically. Results. Compared to euthyroid cases, hypothyroid ones were presenting mostly with amenorrhea (OR=7.76). Other gynecologic manifestations that were prominent in hypothyroid cases were dysparunia, PCO, PMS and Breast tenderness. On the other hand, rate of menstrual irregularities and infertility were non-significantly different in both groups. Hypothyroid women showed also significantly higher frequency of urticaria and puffiness of hands and feet (both were present in 16.7% in hypothyroid vs. 3.3% of euthyroid cases, p =0.007, OR=5.8). Hypothyroid cases showed also significantly higher frequency of yellow ivory skin (OR=5.4) and coarse rough dry skin (OR=3.8). On the other hand, alopecia and periorbital edema were observed only among cases of hypothyroidsm and none of euthyroid cases. Conclusion. A great index of suspicion should be always exerted to the diagnosis of disorders manifesting with subtle manifestations as hypothyroidism in female cases particularly having gynecologic and dermatologic disorders. Key words: dermatologic manifestations, hypothyroidism, gynecologic problems